PEMETAAN ZONA INTRUSI DI JAKARTA - Riadi, Bambang (MAJALAH ILMIAH GLOBE, 2000)
Pertumbuhan penduduk mempunyai berbagai efek, tumbuhnya pemukiman dan urbanisasi. Di wilayah pesisir menurunnya kualitas airtanah akibat intrusi dan pola penggunaan lahan. Jakarta sebagai Ibukota negara berada diwilayah pesisir, wilayah ini mengalami problem intrusi dan juga amblasnya permukaan tanah. Teknik Penginderaan Jauh dan analisa kandungan chloride air tanah yang diambil dari sumur-sumur diseputar Jakarta dikombinasikan dengan peta dapat menunjukan indikasi daerah Jakarta yang teintrusi oleh air laut.ABSTRACTThe increase of population has many effects, such as rapid growth of settlements and urbanizations. ln the coastal region, degradation of water quantity due to saltwater intrusion effects the land use pattern. Jakarta region the capital city of The Republic of Indonesia is also in coastal region, that city has saltwater intrusion problems at soon as land subsidence. Remote sensing Technique and resulted examination chloride content of water sample, compile into map to show indicate salt intrusion area. Kata Kunci : Pemetaan Intrusi Air LautKeywords: Mapping, Salt Intrusion